Fabrication and performance evaluation of low to medium porosity closed-cell porous aluminum via powder metallurgy technique / Nur Ayuni Jamal - Nur Ayuni , Jamal (2016)
In recent years, closed-cell porous Aluminum (Al) have drawn increasing attention, particularly in the applications that require reduced weight and energy absorption capability such as in the automotive and aerospace industries. In the present research, porous Al with closed-cell structure was successfully fabricated by powder metallurgy technique using polymethylmetacrylate (PMMA) as a space holder. The effects of different processing parameters such as PMMA content, compaction pressure and sintering time on the porosity, density, microstructure and compressive behaviors of the porous specimens were systematically evaluated. Under this powder metallurgy technique, similar compaction method but different processing conditions such as mixing equipments, binder types, sintering profiles and optimization techniques were utilized in the preparation of closed-cell porous Al. Specifically, this research was divided into two phases namely as Phase 1 and Phase 2. The porous specimens were characterized through density measurement, X-ray diffraction (XRD), thermogravimetric/differential thermal (TG/DT) analyzer and compressive behavior determination. In addition, the microstructural evolutions of the sintered porous structure were also examined by field emission scanning electron microscopy (FESEM) equipped with energy dispersive spectroscopy (EDS). Based on the findings in Phase 1, different processing parameters such as space holder content and sintering time were selected for further study in Phase 2. The results showed that closed-cell porous Al having different porosities and densities could be produced by varying the amount of PMMA. The addition of PMMA particle as the space holder material during fabrication reduced the density of the porous Al and consequently increased the porosity of the porous specimen. FESEM images revealed successful formation of closed macro-pores structure that replicated the initial morphology of the spherical PMMA particle especially in the case of 25 wt. % and 30 wt. % of PMMA. On the other hand, the highest density and compressive strength of porous specimen were achieved with 300 MPa compaction pressure and 1.5 hr sintering. Prolong sintering to 2.5 hr however was found to deteriorate the sintered density and porosity of the resultant porous Al with no clear effect on their porosity level. In contrast, highest porosity was obtained at 2 hr sintering and 250 MPa compaction pressure at any given PMMA content. Based on the maximum porosity (essential in energy absorption capacity) obtained with the abovementioned processing conditions, the energy absorption values were calculated from the area under the stress-strain curves of porous specimen with different PMMA content. The stress-strain curves demonstrated that the plateau stress decreased and the energy absorption capacity increased with increasing amount of PMMA. However, the maximum energy absorption capacity was achieved in the closed-cell porous Al with the addition of 25 wt. % PMMA. Therefore, fabrication of closed-cell porous Al using 25 wt. % PMMA, 2 hr sintering and 250 MPa compaction pressure are considered as the optimal condition in the present study since the resultant closed-cell porous Al possessed good combinations of porosity, density and plateau stress, as well as energy absorption capacity.